Balanced Nutrition Education and Consultation of Elderly Health Problems in Banjar Tegal Jaya, Badung Bali - Kusumaningsih, Purwaningtyas; Yogeswara, Ida Bagus; Nursini, Ni Wayan; Mantra, Ida Bagus (MITRA: Jurnal Pemberdayaan Masyarakat, 2024)
The health problems of the elderly have become an important concern for the government and society. Especially those who have care for elderly family members at home or nursing homes. Elderly Posyandu is one way to facilitate the elderly to stay active, interact and get health services. Doing exercise, health consultations, and counseling as activities that bring togetherness for the elderly. Health problems that often arise in the elderly such as decreased their appetite and digestive disorders are characterized by difficulty on defecating or has irregular frequence. Decreased the appetite will affect on the imbalance of nutritional intake, lack of sources of fiber, which causing digestive problems, malnutrition and other health problems. The purpose of this service is to remind the elderly about the importance of maintaining a balanced diet. Answer the problems faced by the elderly on a daily basis and provide input, especially for consuming healthy food every day according to the health conditions of the elderly. At the end of the implementation of this service activity, it will help improve the quality of life of the elderly in Banjar Tegal Jaya to be healthier and happier.